Divergent disease patterns in granulocyte-macrophage colony-stimulating factor transgenic mice associated with different transgene insertion sites. - Metcalf, D (1988)
A comparison was made of disease development in two lines of transgenic mice in which the granulocyte-macrophage colony-stimulating factor (GM-CSF) transgene was inserted in different chromosomal locations. Female-line mice (X chromosome insertion) had equivalent elevations of serum GM-CSF levels to those in male-line mice (autosomal insertion) but a shorter survival (median survival, 95 versus 145 days) and a significantly higher incidence of large inflammatory foci in skeletal muscle and gut congestion. Male-line transgenic mice had higher levels of cells in the peritoneal cavity and a higher frequency of spleen enlargement with excess erythropoiesis than female-line mice and uniquely developed fibrotic nodules in the abdominal and pleural cavities. The various diseases in GM-CSF transgenic mice are likely to have been induced by GM-CSF-stimulated products of macrophages, and in the two transgenic lines the macrophages exhibit characteristic differences in morphology and possibly functional activity.